(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article analyzes the theoretical foundations of a competency approach, its historical roots and significance in the modern educational system. At the same time, strategies for the formation and implementation of this approach in pedagogical activity are developed, based on historical and pedagogical sources. The stages of development of the competency approach, its integration into the national education system and its connection with modern pedagogy are analyzed in depth.